Model Pembelajaran Variatif (MPV) Yang Memberdayakan Multiple Intellegince AUD Dalam Belajar Bahasa Inggris - Suratmi, Nanik (Jurnal Inspirasi, 2013)
The crucial problems appeared in the teaching learning process in Kindergarten are dominated not only by the lack of teacherâsÂ professional competency, but also the ego of both parent and school leaders. All of these may violate the multiple intelligence AUD, and ,then, they areÂ drawn from his nice world that is playing. This study is done in order to know the implementation of MPV as a model creating for developing multiple intelligence AUD and returning to the true function of Kindergarten as a beautiful place for learning by playing. The design used is action research based on naturalistic-qualitative. The instrumentsÂ used are the researcher as the main instrument, observation, and photographs. The result ofÂ data analysisÂ showed that are not onlyÂ the two hypotheses are accepted but also the four research problems are solved.Â Kata kunci: MPV, Multiple Intelligence, AUD